Notarial testimonies on the art of silk in Toledo at the beginning of the 16th century (1503-1516) (Edad Media. Revista de Historia, 2022)
This work analyzes the notarial records of Toledo from the beginning of the 16th century. It aims to provide further insight on the silk industry in a thirteen-year period that coincides with its expansion and development. It also aims to evaluate the social, economic and labor aspects of the silk industry.
Keywords: Notaries; Silk; Craftsmen; Production; Trade